Human Resource Management PT Nestle Indonesia Panjang Factory, Lampung, Indonesia - Burhanuddin, Burhanuddin (International Humanity Advance, Business & Sciences, 2024)
The aims of this study were to (1) determine the implementation of the basic functions of management, namely planning, organizing, actuating, and supervising at the Agriculture Office of PT Nestlé Indonesia-Panjang Factory and (2) knowing the implementation of operational functions in the field of human resources, namely procurement, development, compensation , integration, maintenance and termination of labour for human resources in the Agricultural Service Department of PT Nestlé Indonesia-Panjang Factory. This research was conducted using other literature studies where data were obtained through interviews, observation, data recording, direct observation and field work as well as conducting literature studies. The results of this study are that the implementation of basic functions or human resource management at the Agricultural Service Department of PT Nestle Indonesia Panjang Factory has been carried out properly. Procurement of labor at the PT Nestle Indonesia Panjang Factory Agriculture Service is based on the need for labor.